INTEGRASI PENYEMBUHAN DIRI DAN PSIKOEDUKASI DARI SUDUT PANDANG AL-QUR'AN TERHADAP MAKNA HIDUP DAN KESIAPAN UNTUK PERCAKAPAN AKHIR HAYAT (REOLC) PADA LANSIA - Hartati, Elis (Jurnal Ilmu Keperawatan Komunitas, 2025)
This research aims to analyze the effect of integrating self-healing and psychoeducation from perspective of Al Qur'an on the meaning of life and readiness for end-of-life conversations (REOLC) elderly. The method used was quasi experimental pretest-posttest with control group design. The instruments used in this research were the Meaning in Life Questionnaire (MLQ) and Readiness For End Of Life Conversations (REOLC) instruments. The results of the research before and after treatment regarding the meaning of life had a significant difference using the Wilcoxon statistical test, namely W = 194.500, with p < 0.001 and a strong relationship effect Rank-Biserial Correlation = -0.819. And the results before and after treatment regarding Readiness towards death obtained W = 103,000: The Wilcoxon statistical value, has a greater difference after treatment with z = -6.266, has a very significant difference p < 0.001 with a very strong effect namely Rank-Biserial Correlation = -0.901 and SE Rank-Biserial Correlation = 0.143. Conclusion, the integration of self-healing and psychoeducation from perspective of Al Qur'an has a very strong effect and can be used as a method to increase the meaning of life and Readiness For End Of Life Conversations elderly